2021
DOI: 10.1126/sciadv.abe3445
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR-Cas9 screen identified KLF11 as a druggable suppressor for sarcoma cancer stem cells

Abstract: Cancer stem cells (CSCs) are involved in tumorigenesis, recurrence, and therapy resistance. To identify critical regulators of sarcoma CSCs, we performed a reporter-based genome-wide CRISPR-Cas9 screen and uncovered Kruppel-like factor 11 (KLF11) as top candidate. In vitro and in vivo functional annotation defined a negative role of KLF11 in CSCs. Mechanistically, KLF11 and YAP/TEAD bound to adjacent DNA sites along with direct interaction. KLF11 recruited SIN3A/HDAC to suppress the transcriptional output of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Overexpression of transglutaminase‐2 increases the stemness of OSCs, thereby increasing migration and invasiveness (Fuja et al, 2018). There are other genes that change the metastatic ability of osteosarcoma by changing the stemness of OSCs (Han et al, 2020; Jiang et al, 2017; Qu et al, 2018; Y. Wang et al, 2021; Yao et al, 2020; Zhao et al, 2019).…”
Section: Genes Related To Oscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of transglutaminase‐2 increases the stemness of OSCs, thereby increasing migration and invasiveness (Fuja et al, 2018). There are other genes that change the metastatic ability of osteosarcoma by changing the stemness of OSCs (Han et al, 2020; Jiang et al, 2017; Qu et al, 2018; Y. Wang et al, 2021; Yao et al, 2020; Zhao et al, 2019).…”
Section: Genes Related To Oscsmentioning
confidence: 99%
“…In addition, genes can also regulate the metastasis of osteosarcoma cells by changing the stemness of OSCs. KLF11 inhibits the metastasis of sarcoma stem cells by inhibiting the expression of YAP (Y. Wang et al, 2021). Long non‐coding RNA DANCR increases the stemness of OSCs and promotes the metastasis of OSCs by upregulating AXL through competitive binding to miR‐33a‐5p (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…KLF8 and KLF11 have also been shown to be involved in OS cancer stem cell induction [ 185 , 186 ]. KLF8 is highly expressed in OS tissues and highly enriched in CD133-positive cancer stem cell populations [ 185 ].…”
Section: Role Of Klfs In Osteoarthritis Osteoporosis and Osteosarcomamentioning
confidence: 99%
“…KLF11 has previously been shown to play a crucial negative role in cancer stem cells in non-OS tumors [ 190 ]. Through genome-wide screening, Wang et al recently identified KLF11 as a top-hit suppressor molecule in OS cancer stem cell induction [ 186 ]. Mechanistically, KLF11 was associated with yes-associated protein (YAP)/TEA domain family member 1 (TEAD) at adjacent DNA sites, where KLF11 suppressed YAP/TEAD functions by recruiting the SIN3 transcription regulator family member A (SIN3A)/histone deacetylase (HDAC) repressor complex [ 186 ].…”
Section: Role Of Klfs In Osteoarthritis Osteoporosis and Osteosarcomamentioning
confidence: 99%
“…Compared with previous functional deletion screening systems, the CRISPR/Cas9 screening system has higher sensitivity, higher data reproducibility and minimal off-target effects. In recent years, CRISPR/Cas9 library screening has been used in various models to identify genes that are critical for cancer cell survival, proliferation, migration, and drug resistance [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%